Tidal and river discharge forcing upon water and sediment circulation at a rock-bound estuary (Guadiana estuary, Portugal) - Garel, E. (2009)
The relative impacts of tidal (neap, spring) and river discharge (including a flood event) forcing upon water and sediment circulation have been examined at the rock-bound Guadiana estuary. Near-bed and vertical profiles of current, salinity, turbidity, plus surface suspended sediment concentrations (SSC, at some stations only), were collected at the lower and central/upper estuary during tidal and fortnightly cycles. In addition, vertical salinity and turbidity profiles were collected around high and low water along the estuary. Tidal asymmetry produced faster currents on the ebb than on the flood, especially at the mouth. This pattern of seaward current dominance was enhanced with increasing river flow, due to horizontal advection that was confined within the narrow estuarine channel. The freshwater inputs and, at a degree less, the tidal range controlled the vertical mixing and stratification importance. Well-mixed (spring) and partially stratified (neap) conditions alternated during periods of low river flows, with significant intratidal variations induced by tidal straining (especially at the partially stratified estuary). Highly stratified conditions developed with increasing river discharge. Intratidal variability in the pycnocline depth and thickness resulted from current shear during the ebb. A salt wedge with tidal motion was observed at the lower estuary during the flood event. Depending on the intensity of turbulent mixing, the residual water circulation was dominantly controlled either by tidal asymmetry or gravitational circulation. The SSC was governed by cyclical local processes (resuspension, deposition, mixing, advection) driven by the neap-spring fluctuations in tidal current velocities. More, intratidal variability in stratification indicated the significance of tidal pumping at the partially and highly stratified estuary. The estuary turbidity maximum (ETM) was enhanced with increasing current velocities, and displaced downstream during periods of high river discharge. During the flood event, the ETM was expelled out of the estuary, and the SSC along the estuary was controlled by the sediment load from the drainage basin. Under these highly variable river flow conditions, our observations suggest that sand is exported to the nearshore over the long-term (>years).